Effect of the addition of red beans and arabic gum on the quality of corn milk - Misail Meliala; Ismed Suhaidi; Rona Joharmi Nainggolan (Universitas Sumatera Utara, 2014)
This study was conducted to determine the process of making of corn milk with the addition of red beans and arabic gum. This research was conducted using a completely randomized design with two factors, namely the number of red beans; 0%, 10%, 20% and 30% of the weight of the corn and the concentration of arabic gum ; 0%, 0,1%, 0,2% and 0,3%. The parameters analyzed were fat content, protein content, total solids, viscosity, pH, organoleptic of color, aroma and flavor. The results showed that the amount of red bean had highly significant effect on levels of protein, total solids, viscosity and aroma and had no significant effect on fat content, pH, color and flavor. Concentration of arabic gum had highly significant effect on total solids and viscosity, and had significant effect on protein content and had no different effect on fat content, pH, organoleptic color, aroma and flavor. Interaction of the amount of red bean and arabic gum had highly significant effect on total solids and viscosity, and had no significant effect on fat content, protein content, pH, organoleptic color, aroma and flavor. Amount of red beans of 30% and 0,3% of arabic gum produced the best quality of corn milk. Keywords: arabic gum, corn milk, red beans.